PERBANDINGAN ISOLASI MINYAK ATSIRI DARI BUNGA KENANGA (Cananga odorata (Lam.) Hook.f & Thoms) CARA KONVENSIONAL DAN MICROWAVE SERTA UJI AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN - Fela Tri Anggia; Yuharmen '; Nur Balatif (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Cananga odorata (Lam.) Hook.f & Thoms plants were one of essential oil sources wich has an antibacterial and antioxidant activity. In the research, isolation of essential oil from Cananga odorata (Lam.) Hook.f & Thoms was carried out with traditional hydrodistillation method and microwave method. The optimalcondition in the traditional method was 4 hours, while the optimal condition in the microwave method were 100o C, 40 minutes and 600 W. Isolation of the essential oil from Cananga odorata (Lam.) Hook.f & Thoms using microwave method produced higher yield (1,08%) compared to the traditional method (0,62%). The essential oil from Cananga odorata (Lam.) Hook.f & Thoms was indentified by GC-MS and resulted 35 compounds for traditional method and 53 compounds formicrowave method. Antibacterial activity assay showed equal result for both methods, that the Gram-negative bacteria (Salmonella enteritidis, Staphylococcus aureus) were more active in inhibiting the growth of bacteria compared to Grampositivebacteria (Escherichia coli, Bacillus subtilis). The antioxidant activity assay of the essential oil from Cananga odorata in the microwave method (884,31 µg/mL) was better than that of the traditional method (883,78 µg/mL).